2015
DOI: 10.4103/0974-9233.148351
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Ahmed valve implant following a failed initial trabeculotomy and trabeculectomy in refractory primary congenital glaucoma

Abstract: Purpose:The aim was to report the outcome of Ahmed glaucoma valve (AGV) (New World Medical, Inc., Rancho Cucamonga, CA, USA) implantation as a surgical intervention following an initial failed combined trabeculotomy + trabeculectomy (trab + trab) in refractory primary congenital glaucoma (RPCG).Materials and Methods:Retrospective chart review of 11 eyes of 8 patients who underwent implantation of AGV (model FP8) for RPCG between 2009 and 2011. Prior trab + trab had failed in all the eyes. Success was defined a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 25 publications
(34 reference statements)
0
25
0
Order By: Relevance
“…The use of anti-metabolites, such as mitomycin C (MMC), in PCG patients has been reported in some studies to improve success rates of surgery, quoted as 52–82% 73, 74. The use of MMC is preferred in refractory cases, aphakic eyes, and older children 75, 76, 79. Although some are doubtful about the application of MMC in children, evidence suggests that its use is safe and postoperative complications encountered are similar to those seen in adults 76, 77.…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…The use of anti-metabolites, such as mitomycin C (MMC), in PCG patients has been reported in some studies to improve success rates of surgery, quoted as 52–82% 73, 74. The use of MMC is preferred in refractory cases, aphakic eyes, and older children 75, 76, 79. Although some are doubtful about the application of MMC in children, evidence suggests that its use is safe and postoperative complications encountered are similar to those seen in adults 76, 77.…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…Retrospective studies on Ahmed glaucoma valve (AGV) revealed a 28 to 49% reduction in the mean IOP and a success rate ranging from 63 to 97% at 1 year. 66 - 68 The definition of success is similar across studies, which is defined as absence of serious complications or lost of light perception, with an acceptable IOP with or without the use of medication, thought the acceptable IOP ranges from 18 to 23 mm Hg across studies. 66 - 68 Hispanic ethnicity and gender female have been reported to be independent predictors for failure of the GDD procedure, but the underlying reason has yet to be identified.…”
Section: Treatmentmentioning
confidence: 99%
“… 73 It has been suggested that GDD may be preferable to trabeculectomy when conjunctival scarring is evident, 74 or in buphthalmic eyes with very thin sclera. 66 It is hypothesized that as the bleb is located more posteriorly in GDD, the long-term risk of infection is, thus, theoretically lower. 66 However, GDD is associated with more complications that requires re-operation than trabeculectomy (46% vs 13%), in particular displacement of tube leading to tube-endothelial touch and tube retraction.…”
Section: Treatmentmentioning
confidence: 99%
“…Furthermore, these patients used a significantly lower number of medications postoperatively (1.6 vs. 2.6 preoperatively), as our patients did. The referred complications included shallow anterior chamber with choroidal detachment at 1 week, which resolved spontaneously with medications, tube corneal touch and tube retraction(15).…”
mentioning
confidence: 99%